AN ANALYSIS OF THE FIRST YEAR STUDENTS’ ABILITY TO WRITE PRESENT CONTINUOUS TENSE IN SIMPLE SENTENCES TRIGGERED BY PICTURES AT SMK KARTIKA 1-2 PADANG - Ayu Oktaviani (LP4MK STKIP PGRI Lubuklinggau, 2016)
The purpose of this research was to find out the ability of the first students to write present continuous sentences triggered by picture. In specific the purposes of this study are as follows: 1. to describe the students’ ability of SMK Kartika 1-2 Padang to write positive form sentences in present continuous tense triggered by pictures. 2. to describe the students’ ability of SMK Kartika 1-2 Padang to write negative form sentences in present continuous tense triggered by pictures. 3. to describe the students’ ability of SMK Kartika 1-2 Padang to write interrogative form sentences in present continuous tense triggered by pictures. The design of this study was a descriptive in nature. According to Gay (1987:189), descriptive research involves collecting data in order to answer question concerning the current status of the subject of the study. The instrumentation that used to collect the data in this research was writing test. It consisted of 20 pictures. In this test, the students were required to write present continuous in simple sentences (positive sentences, negative sentences and interrogative sentences) triggered by pictures. Based on the result of the study, in general, the students’ ability to write present continuous tense in simple sentences triggered by pictures was moderate since there were 24 students (55.81%) from 43 students had moderate ability. Data also exhibited that their ability to write positive form, negative form, and interrogative form was moderate with percentages as follow: 69.77% for positive form present continuous tense sentences triggered by pictures, 67.44% for negative form present continuous tense sentences triggered by pictures and 76.74% for interrogative form present continuous tense sentences triggered by pictures.